Aplikasi Sistem Payroll Menggunakan Framework Codeigniter Berbasis Web - Rizal Rachman; Haris Ramadhan; Komarudin Komarudin (LPPM STMIK Mardira Indonesia, 2022)
Employees are an important subject in an organization. One of them is part of Human Resource which is responsible for managing personnel data. Management of personnel still manual So that the company is struggling to get information related to personnel employee. The other problems are not optimal to create of employee salary report. For solve with these problems, human resource application that can help the HRD and supervisor to perform the task. The creation of this web-based application uses waterfall methods that include: analysis, design, coding and testing using the PHP framework Codeigniter and MySQL as the database. From the results of the research was obtained that Human Resource information system makes information received faster, management of personnel data, Payroll data is easier and the process of creating employee salaries can be done quickly and according to the schedule.